Nutritional value and inclusion levels of residual annatto seed meal in diets for Japanese quails - Pimentel-Mani, Iana; Oliveira, Maria C.; Lima-Dóro, Sarah C. O.; Carneiro-Martins, Poliana; Souza-Júnior, Marcos A. P. (Revista Colombiana de Ciencias Pecuarias, 2019)
Background: Residual annatto seed meal (RASM) is a byproduct after extraction of bixin in the cosmetic industry and may be used in animal diets. Objective: Two experiments were carried out to determine the nutritive value and effect of RASM inclusion levels in the diets of Japanese quails. Methods: For the digestibility experiment, 160 Japanese quails were distributed in a randomized study with two treatments and 10 replicates with eight birds each. The treatments consisted of a reference diet and a test diet containing 75% of the reference diet and 25% of RASM. For the performance assay, 192 Japanese quails were used in a randomized study with six treatments and four replicates with eight birds each. Treatments consisted of a control corn-based diet (Contr1) and another diet based on sorghum + canthaxanthin (Contr2), and four diets based on sorghum with increasing inclusion levels of RASM (0, 3, 6, and 9%). Results: Digestibility of dry matter and crude protein, metabolization coefficient of gross energy, and retention of calcium and phosphorus were 41.05, 43.12, 47.97, 25.49, and 30.35%, respectively. RASM inclusion did not influence bird productivity; however, feed conversion worsened in treatments with 0–6% RASM inclusion relative to that in Contr1. Yolk color increased due to RASM treatment. Conclusion: RASM may be included in sorghum-based diets for quails at 9%, with improvement in yolk color and no negative effects on productivity and egg quality.